2011
DOI: 10.1016/j.amjcard.2011.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Visceral Adiposity to Circulating Natriuretic Peptides in Ambulatory Individuals

Abstract: Natriuretic peptides have important roles in the regulation of vasomotor tone, salt homeostasis, and ventricular remodeling. Lower natriuretic peptide levels observed in obese individuals may underlie the greater cardiovascular risk associated with obesity. Thus, the aim of this study was to determine whether lower natriuretic peptide levels in obesity are attributable to differences in regional fat distribution. We investigated the relationship of plasma N-terminal pro-B-type natriuretic peptide (N-BNP) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 29 publications
1
51
0
3
Order By: Relevance
“…7 Another biological plausible mechanism linking VAT to human hypertension involves decreased activity of the NP system. It is well known that obese individuals have lower circulating NP concentrations, but studies from both the Dallas Heart Study 10 and the Framingham Heart Study 39 showed that increased VAT, determined by MRI or CT, in contrast to SAT, was significantly negatively associated with circulating concentrations of B-type natriuretic peptide and N-terminal pro-B-type natriuretic peptide after multivariate adjustment. On the basis of these findings, it is reasonable to suggest that the lower amount of circulating B-type natriuretic peptide associated with increased VAT, resulting in diminished vasodilation and natriuresis, 40 could be involved in the pathogenesis of increased VAT-related hypertension in early stages of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another biological plausible mechanism linking VAT to human hypertension involves decreased activity of the NP system. It is well known that obese individuals have lower circulating NP concentrations, but studies from both the Dallas Heart Study 10 and the Framingham Heart Study 39 showed that increased VAT, determined by MRI or CT, in contrast to SAT, was significantly negatively associated with circulating concentrations of B-type natriuretic peptide and N-terminal pro-B-type natriuretic peptide after multivariate adjustment. On the basis of these findings, it is reasonable to suggest that the lower amount of circulating B-type natriuretic peptide associated with increased VAT, resulting in diminished vasodilation and natriuresis, 40 could be involved in the pathogenesis of increased VAT-related hypertension in early stages of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced natriuretic peptide levels have previously been observed in a number of conditions including obesity, diabetes mellitus, and insulin resistance (28-33). These conditions are more common among black individuals and while some studies suggest that blacks may have lower natriuretic peptide levels than whites (16-20), these prior reports did not specifically focus on race/ethnic differences in natriuretic peptide levels while accounting for comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Framingham Heart Study, the inverse relationship between NT-pro-BNP and abdominal adipose tissue mass was stronger for visceral, compared to subcutaneous, adiposity (33). Furthermore, lower BNP concentrations have been associated with the metabolic syndrome and its components, even after statistical adjustment for obesity (9,34,35).…”
Section: Discussionmentioning
confidence: 99%